SPANISH MILITARY EDUCATION – ARMY OFFICER BASE LINE - DE BAÑOS CARRILLO Antonio M.; NÚÑEZ Francisco G. (2020)
Spain is having new winds of changes in the field of education and consequently the army is not an exception in the way this institution is adapting new teaching-learning bases. Although the 21st century is bearing to new models and procedures in pedagogy we cannot lose the track and forget how cadets are taught and how cadets are learning, and less now in this new biological atmosphere. The aim of this article is to provid an analysis of Spanish military education and overviews its evolution.